Pengaruh Persepsi Mahasiswa Tentang Profesi Guru, Efikasi Diri dan Lingkungan Keluarga Terhadap Minat Menjadi Guru - Sundari, Tri; Ningsih, Sulistio; Yanti, Safridha; Sari, Desi Purnama; Tonara, Arda (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2024)
Education has an important role in long-term investment in human life and is the key to future success. Teachers are the most important component in achieving educational goals. The level of someone's interest in becoming a teacher is influenced by many factors that influence the professionalism of a teacher's performance. The problem in this research is whether students' perceptions of the teaching profession, self-efficacy, and family environment influence their interest in becoming a teacher. The study aims to determine the influence of Student Perceptions of Teacher Profession, Self Efficacy, and Family Environment on the interest of being a Teacher in Economic Education Students at Muhammadiyah Mahakarya University of Aceh. Sampling techniques use total sampling because the population of this study is less than 100. The data analysis technique used is multiple regression analysis. Study results showed that Student Perceptions of Teacher Profession, Self Efficacy, and Family Environment partially had no significant influence on Interest in being a teacher. While simultaneously Student Perception of teacher profession, self efficacy, and family environment influenced the Teacher Interest variable with a percentage of 81.7%, while the remaining 18.3% could be described by other variables not studied by the researchers